STUDI PENGARUH WAKTU PEMERAMAN DAN KUAT TEKAN PAVING BLOCK DENGAN BAHAN DASAR TANAH LEMPUNG LUNAK, SEMEN DAN KAPUR MENGGUNAKAN ALAT PENETRASI MODIFIKASI - wiguna, rifan; setyanto, setyanto; adha, idharmahadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
The use of paving blocks (concrete bricks) is widely used for various elements of building construction, on paving block work is often used for pavement road pavement, yard and public facilities, environmental roads and various other needs. This research is curing the paving block. This is intended for the maintenance of paving blocks using clay soil with lime and cement with varying curing time ie curing for 7 days, 14 days, 21 days, and 28 days with the aim of analyzing the optimum time of addictive substances ie cement and lime in Binding of particles. Based on the analysis, the cement and lime material greatly affect the value of compressive strength to paving block, at optimum curing time of 14 days, the highest value of compressive strength in post-burn samples of 12.58 Mpa and pre-burn of 6.92 MPa, with compressive strength value In the postburn sample the paving bloc now meets the quality standard c which can be applied to pedestrians based on SNI 03-0691-1996. Similarly, the results of the combustion of samples for 2 x 24 hours gained the compressive strength of the paving block is higher than the sample that is not done burning. The result of absorption value of paving block ranges from 7 - 9% hence absorption paving block fulfill specification of absorption value of paving block based on SNI 03-0691-1996 which is 3-10%.Keywords : paving block, organic clay oil, compressive strength, water absorption, brooded